The prevalence of bovine mastitis-associated Staphylococcus aureus in China and its antimicrobial resistance rate: A meta-analysis - Wang, Kuan; Cha, Jinlong; Liu, Kai; Deng, Jianming; Yang, Bowen; Xu, Hui; Wang, Juyu; Zhang, Limei; Gu, Xiaolong; Huang, Cuiqin; Qu, Weijie (Frontiers in Veterinary Science, 2022)
In this study, to optimize the Staphylococcus aureus control program, a meta-analysis was conducted to investigate the epidemiology and antimicrobial resistance (AMR) profile of S. aureus-associated bovine mastitis in China from 2000 to 2020. A total of 33 publications from PubMed, Google Scholar, and China National Knowledge Infrastructure (CNKI) database were included in our research, among which nine publications included the AMR test. The pooled prevalence of S. aureus was 36.23%, and subgroup analysis revealed that the prevalence dropped from 2000–2010 to 2011–2020, which shows that China is on the right track. The pooled AMR rate indicate isolates were most resistant to β-lactams (50.68%), followed by quinolones (36.23%), macrolides (34.08%), sulfonamides (32.25%), tetracyclines (27.83%), aminoglycosides (26.44%), lincosamides (23.39%), and amphenicol (10.33%). Both the pooled prevalence and AMR of S. aureus in China are higher than those in Western countries, such as Germany, Belgium, Ireland, and the United States—countries with a long animal husbandry history and good management. Thus, there is still room to improve the treatment of S. aureus-associated bovine mastitis in China.